2009
DOI: 10.1038/nn.2329
|View full text |Cite
|
Sign up to set email alerts
|

βCaMKII controls the direction of plasticity at parallel fiber–Purkinje cell synapses

Abstract: We found that betaCaMKII, the predominant CaMKII isoform of the cerebellum, is important for controlling the direction of plasticity at the parallel fiber-Purkinje cell synapse; a protocol that induced synaptic depression in wild-type mice resulted in synaptic potentiation in Camk2b knockout mice and vice versa. These findings provide us with unique experimental insight into the mechanisms that transduce graded calcium signals into either synaptic depression or potentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
144
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(173 citation statements)
references
References 15 publications
27
144
2
Order By: Relevance
“…We found no significant change in the density of spines (wild-type mice: 6.35 Ϯ 0.36 n ϭ 15 cells from 3 mice; Camk2b Ϫ/Ϫ mice: 7.07 Ϯ 0.61 n ϭ 15 from 3 mice; unpaired two-tailed t test, t (28) ϭ 1.8, p ϭ 0.09) (Fig. 1d), which is consistent with our previous findings for the cerebellum (van Woerden et al, 2009). Together, these data show that gross neuronal development is preserved in Camk2b Ϫ/Ϫ mice.…”
Section: Camk2bsupporting
confidence: 92%
See 1 more Smart Citation
“…We found no significant change in the density of spines (wild-type mice: 6.35 Ϯ 0.36 n ϭ 15 cells from 3 mice; Camk2b Ϫ/Ϫ mice: 7.07 Ϯ 0.61 n ϭ 15 from 3 mice; unpaired two-tailed t test, t (28) ϭ 1.8, p ϭ 0.09) (Fig. 1d), which is consistent with our previous findings for the cerebellum (van Woerden et al, 2009). Together, these data show that gross neuronal development is preserved in Camk2b Ϫ/Ϫ mice.…”
Section: Camk2bsupporting
confidence: 92%
“…Inducible overexpression of ␤CaMKII in the dentate gyrus did not affect acquisition of hippocampal learning, but did affect the long-term consolidation of memories (Cho et al, 2007). Additionally, it was shown that the absence of ␤CaMKII reverses the polarity of plasticity at cerebellar parallel fiber-Purkinje cell synapses and causes significant cerebellar learning deficits (van Woerden et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It is believed that memory is supported by the balance between the formation and recovery processes (42). Previous studies have shown that kinases (43,44) and phosphatases (33) act as switches of synaptic plasticity, thus regulating memory formation and reversal processes (45,46). Thus, the slow formation of memory by massed training may allow strong reversal processes and induce the rapid decay of long-lasting memory, whereas the rapid formation of memory observed in spaced training may strongly suppress reversal processes.…”
Section: Discussionmentioning
confidence: 99%
“…β-CaMKII is expressed in Purkinje cells as well (28), but the inhibitory autophosphorylation has only been examined in α-CaMKII and has been shown to have a dominant negative effect on the holoenzyme (27). Both α-CaMKII and β-CaMKII are essential for proper LTD induction (28,29). CaMKII promotes LTD by suppressing the activity of protein phosphatase 2A through negative regulation of phosphodiesterase 1 and subsequent disinhibition of a cGMP/protein kinase G pathway (30).…”
Section: Significancementioning
confidence: 99%